2009
DOI: 10.1080/00048670902873664
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Combination Therapy Versus Antidepressant Therapy for Management of Depression in Japan

Abstract: The combined therapy appeared to be cost-effective from the health-care system perspective and the dominant strategy from the social perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…All studies considered intervention costs, while 5 studies reported outpatient costs additionally [20,21,22,24,25]. Four studies included inpatient costs and medication [21,22,24,25]. Simon et al [21] and Morrell et al [25] - employing the perspective of the British National Health Services - considered costs for community health services.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies considered intervention costs, while 5 studies reported outpatient costs additionally [20,21,22,24,25]. Four studies included inpatient costs and medication [21,22,24,25]. Simon et al [21] and Morrell et al [25] - employing the perspective of the British National Health Services - considered costs for community health services.…”
Section: Resultsmentioning
confidence: 99%
“…Costs were assessed from a third-party payer perspective mainly. All studies considered intervention costs, while 5 studies reported outpatient costs additionally [20,21,22,24,25]. Four studies included inpatient costs and medication [21,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations